2018
DOI: 10.1038/s41598-017-18561-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced nasal drug delivery efficiency by increasing mechanical loading using hypergravity

Abstract: Nasal route drug administration for local and systemic delivery of many therapeutics has received attention because the nasal cavity is highly vascularized and provides a large surface area for drug absorption. However, nasal mucosa exhibits limited permeability to polar molecules. In this study, we developed a novel method for improving absorption efficiency of polar drugs by applying hypergravity. RPMI 2650 cells and primary human nasal epithelial cells were exposed three times to a 20 min hypergravitational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Actually in vitro studies showed that hypergravity may be an effective new strategy for that. Such a finding might be of great interest in space pharmacology ( Vernikos, in press ) where enhanced nasal drug delivery in microgravity may be desired ( Kim et al, 2018 ).…”
Section: Pharmaco-kinetics and –Dynamicsmentioning
confidence: 99%
“…Actually in vitro studies showed that hypergravity may be an effective new strategy for that. Such a finding might be of great interest in space pharmacology ( Vernikos, in press ) where enhanced nasal drug delivery in microgravity may be desired ( Kim et al, 2018 ).…”
Section: Pharmaco-kinetics and –Dynamicsmentioning
confidence: 99%
“…That influences the pharmacokinetics of systemically of locally delivered drugs. Increased cellular uptake of therapeutics on skeletal muscle cells or nasal epithelial cells has been reported, when the strain was applied [220,221]. This situation could also apply to bone cells, highlighting the importance of drug screening during applied mechanical loading.…”
Section: Drug Screening In the Presence Of Mechanical Loading Is Critmentioning
confidence: 97%
“…It appeared that the LCC/ALI switch was feasible 24 h after inoculation when starting from a seeding density of 4-5 × 10 5 cells/cm 2 (Pozzoli et al, 2014). Cell differentiation and the presence of tight junctions were effective after two weeks under ALI conditions, with TEER values of 50 and 120 Ω.cm 2 after 1 and 2 weeks, respectively (Kim et al, 2018;Pozzoli et al, 2016a,b).…”
Section: In Vitro Modelsmentioning
confidence: 99%
“…The model was first used for metabolic studies (e.g. degradation tests) and, subsequently, for transport experiments after culture optimization (Gonçalves et al, 2016;Kim et al, 2018;Shin et al, 2004). In fact, RPMI 2650 cells were subject to strong histological modifications when switching from LCC to ALI (e.g.…”
Section: In Vitro Modelsmentioning
confidence: 99%